Tanggung Jawab Penerbit dan Manajer Investasi Terhadap Kasus Gagal Bayar (Default) Dana Investasi Reksadana Yang Dialami Investor : Studi Kasus PT. Tridomain Performance Materials Tbk - Juan Dicky A. Sukatendel; Yudho Taruno Muryanto (Lembaga Pengembangan Kinerja Dosen, 2024)
The capital market is an important part of representing the country's economic conditions. In the capital market there are several instruments that are traded, one of which is mutual funds. Mutual funds are quite an attractive option for the community, but there are cases of default that make mutual fund investors suffer losses. This research uses a normative juridical approach method, namely library legal research conducted by examining library materials or secondary data as a basis for research by conducting a search for laws and literature related to the problems studied. Legal protection can be done by using preventive and repressive legal protection in mutual fund investment cases as a form of protection to investors from the government. The losses suffered by investors due to the default of PT TDPM to MMI, indicate that TDPM has a responsibility that can be in the form of paying all obligations and compensation and accepting all sanctions that can be in the form of administrative, civil, to criminal. Preventive legal protection can be seen in the existence of laws and regulations such as the Capital Market Law, P2SK Law, POJK 48/2015, POJK 31/2015, and others. Repressive legal protection is in the form of enforcement of sanctions from administrative even to bankruptcy. Responsibility must be carried out by TDPM, namely paying obligations along with interest according to the debt restructuring agreement until the imposition of sanctions. And it is necessary to see the form of MMI's responsibility as the Investment Manager in this case.